The Role of the Family in Preventing the Transmission of COVID-19 in Children - Onggang, Fransiskus Salesius; Romana, Aben B.Y.H.; Batbual, Bringiwatty (JURNAL INFO KESEHATAN, 2023)
COVID-19 is a disease that is highly communicable from infected individuals to others who are susceptible to infection. The family is the first line of defense against the spread of the COVID-19 epidemic among youngsters. There is transmission of the COVID-19 virus to children notwithstanding the inadequacy of parental efforts to prevent such transmission. The effect of COVID-19 infection on unfit parents will result in the transmission of the virus to offspring. The incidence of COVID-19 in children is influenced by the level of parental knowledge and conduct to avoid the transfer of the virus. The purpose of this study is to examine the relationship between parents' activities and attitudes regarding COVID-19 prevention, the detection of COVID-19 symptoms in children, and the level of information regarding the prevalence of COVID-19 in children. The research design employs a cross-sectional observational analysis. This study's demographic and sample consisted of proportional samples from 12 Community Health Centers, with 550 family respondents in total. The results of this study indicate that delivering the COVID-19 vaccination to the family considerably reduces the risk of COVID-19 transmission to children. The level of family knowledge correlates strongly with the transmission of COVID-19 to children (a symp=0.001, with a correlation p-value of 0.669). There is a correlation between the administration of the COVID-19 vaccine to parents and the transmission of the virus to children (symp=0.001, p=0.660). Based on the results of the study, there was a significant influence between the level of parental knowledge on the behavior of preventing COVID-19 in children in Kupang City. In addition, there is a significant relationship between the behavior and attitudes of parents who are disobedient in preventing COVID-19 in children and the incidence of COVID-19 in children. Families or parents who carry out the COVID-19 vaccination in the family also have a significant relationship with the transmission of the COVID-19 virus to children. To reduce the transmission of COVID-19 to children, efforts from the family are needed, such as implementing health protocols and carrying out vaccinations.